(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. For the effective organization of marketing activities of the enterprise, it is important to rationally build a product policy, which is the basis for making marketing decisions related to the features of the product purchase and the mechanism of its promotion from the manufacturer to the end consumer. The purpose of the article is an in-depth study of the theoretical and methodological aspects of the analysis and planning of marketing product policy (PMP) by developing the structure of the enterprise’s PMP strategic plan and building a product management model. Methods. Using the method of analysis and synthesis made it possible to propose an own approach to marketing planning of product policy. Results. The article provides a theoretical analysis of literary sources regarding the interpretation of the concept of PMP by various authors, the expediency of marketing analysis and product policy planning is substantiated. Based on the study of foreign experience, the structure of the enterprise’s PMP strategic plan was developed. The relationship between the formation of the PMP «roadmap» and the need to check the maturity of the marketing product policy team, which is represented by such entities and processes as management, employees, PMP implementation tools, business processes and production organization, is presented. Conclusions. Improving MTP planning is one of the most important ways to increase the efficiency of the enterprise. It is important to carry out such marketing planning, which helps to substantiate the impact of the enterprise’s general corporate strategy, business strategies on the product strategy.